Characterisation of binary (NiO)x (Ag2O)1?x nanoparticles synthesised via the thermal treatment route - Absi E.; Hamzah K.; Ahmad N.E.; Jamaluddin K.; Al Hada N.M.; Saleh M.A.; Al-Ghaili A.M.; Shayea I. (Elsevier Ltd, 2024)
In this study, binary nickel oxide silver oxide nanoparticles (NiO)x (Ag2O)1?x (NPs) were synthesised for the first time using the thermal treatment route at higher and lower precursor values. Two precursors and 5 g of polyvinyl pyrrolidone (PVP) were employed to obtain the (NiO)x (Ag2O)1?x NPs at 700 C. The obtained NiO NPs documented cubic and hexagonal phases when assessed with X-ray diffraction (XRD) at (x = 0.4 and 0.6) and (x = 0.2 and 0.8), respectively. The cubic phase was confirmed for Ag2O NPs in all prepared samples. The smallest crystallite and particle sizes were found at x = 0.8. The particle size ranged from 23.0 to 45.0 nm, which was evaluated with a transmission electron microscope (TEM). Two shapes, NiO doped with porous Ag2O nanosheets, were observed with a scanning electron microscope (SEM). The purity of the products was evaluated via energy-dispersive X-ray (EDX) spectroscopy. The synthesised NPs were composed of nickel (Ni), silver (Ag), and oxygen (O). Moreover, the X-ray photoelectron spectroscopy (XPS) analysis performed during this study revealed the chemical states of the Ni, Ag, and O present, which confirmed the purity of the NPs. The ultravioletvisible spectroscopy (UVVis) assessment conducted also demonstrated that the energy band gaps for nickel oxide (NiO) and silver oxide (Ag2O) increased with rising x values. The photoluminescence (PL) analysis performed in this study also verified the existence of two emission peaks attributable to NiO and Ag2O, indicating that the NPs possess good photocatalytic activity. Consequently, the NPs synthesised in the present study could be applied as antimicrobial agents in wastewater treatment. 2023 Elsevier Ltd and Techna Group S.r.l.